Genetic and morphological differences between yellowtail kingfish (Seriola lalandi) from the Bohai Sea, China and the Southern Ocean, Australia - Ai, Qiaoyun; Sang, Longlong; Tan, Hongxin; Huang, Xuxiong; Bao, Baolong; Li, Chenhong (Aquaculture and fisheries, 2021)
The aquaculture of yellowtail kingfish (Seriola lalandi) has expanded around the globe, including China. Genetic resource of Chinese S. lalandi urgently needs to be assessed for improving production. Here, we collected wild S. lalandi samples from the Bohai Sea, China and evaluated its genetic diversity based on 17,690 nuclear loci. A population from the Southern Ocean, Australia was used for comparison. The analyses showed that the Chinese and Australian S. lalandi formed two completely distinct clusters and there was no genetic introgression from the Australian S. lalandi into the Chinese S. lalandi population. The genetic diversity is slightly lower, but comparable in Chinese versus Australian yellowtail kingfish (Chinese population, expected heterozygosity: 0.19, observed heterozygosity: 0.19, nucleotide diversity: 0.19 ± 0.09; Australian population, expected heterozygosity: 0.23, observed heterozygosity: 0.22, nucleotide diversity: 0.22 ± 0.11). Overall, our results indicated that Chinese S. lalandi could be a potential subject for genetic breeding programs. We also investigated morphological characters and developed molecular markers for population identification. Comparison of meristic characters between the Chinese population and the Australian population revealed that main shape difference were in the number of dorsal spines, dorsal fin rays and the number of upper gill rakers. Geometric morphology based on eight landmarks also revealed significant difference between the two populations including the distance between the tip of snout to origin of pelvic fin and the distance between the tip of snout to origin of pectoral fin. These morphological characters can be used for easy identification of the Chinese S. lalandi.